Implementation of Skilled Training Programs at Vocational College: A View of the Instructors’ Perspectives - Mohd Noor, Mohd Shahril; Mohamad, Marlina; Paimin, Aini Nazura (Online Journal for TVET Practitioners, 2023)
The vocational colleges of Malaysia have been running several engineering related programs to certify their students with Malaysian Skills Certificate, Malaysian Vocational Diploma and Malaysian Vocational Certificate. The aim of these programs is to provide competent skilled and knowledge workers for the needs of the local industries in order to foster national development towards achieving developed nation status. To ensure the success of these programs, instructors are expected to be able to conduct training and master the engineering education process. This study was conducted to identify vocational college instructors’ views on the implementation of the skill training programs in the aspects of curriculum, infrastructure and industrial training. A total of 116 technical instructors in the fields of engineering skills namely Welding Technology, Automotive Technology, Electrical Technology, Refrigeration and Air conditioning, Electronic Technology, Industrial Machining and Construction Technology participated in this research. The data were analysed to determine the average mean score of the measured variables. Findings showed that the average mean score for curriculum and industrial training aspects were found to be at high level, while moderate level was obtained for the aspect of infrastructure. This finding implies that professional development programs are less crucial compared to facilities required to run the skill training programs. This issue needs to be addressed by the vocational colleges’ management and government to ensure successful implementation of these skilled training program at college level.